2009
DOI: 10.1007/s10620-008-0707-y
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of MRI in Experimentally Induced Inflammatory Small Bowel Disease: A Pilot Study in a Porcine Model

Abstract: The purpose of this study was to compare the macroscopic and microscopic findings of experimentally induced inflammatory lesions in jejunum and ileum with magnetic resonance imaging (MRI) findings. Inflammatory small bowel lesions were experimentally induced in six pigs. Bowel segments in jejunum and ileum were isolated, and a solution with trinitrobenzenesulfonic acid and ethanol (TNBS-EtOH) was installed. MRI of the small bowel was performed 7 days after surgery. Before the MRI examination, a 6% mannitol sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…This results in a T-cell-dependent mucosal immune response and transmural infiltration of neutrophils (10,25). We observed that the volume of ethanol can be substantially reduced to 0.8 mL (compared with 40 mL, as published previously [22,23]), which caused moderate-to-severe TNBS-mediated inflammation with minimal discomfort to the animals. Another detail worth noting is the need to premedicate pigs with aspirin, indomethacin, or a specific thromboxane receptor blocker before injecting lipid-based particles such as MBs (16)(17)(18), because pigs have abundant intrapulmonary macrophages (26,27).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…This results in a T-cell-dependent mucosal immune response and transmural infiltration of neutrophils (10,25). We observed that the volume of ethanol can be substantially reduced to 0.8 mL (compared with 40 mL, as published previously [22,23]), which caused moderate-to-severe TNBS-mediated inflammation with minimal discomfort to the animals. Another detail worth noting is the need to premedicate pigs with aspirin, indomethacin, or a specific thromboxane receptor blocker before injecting lipid-based particles such as MBs (16)(17)(18), because pigs have abundant intrapulmonary macrophages (26,27).…”
Section: Discussionsupporting
confidence: 78%
“…Pigs are increasingly being recognized as important large-animal models for IBD (21)(22)(23)(24). We modified published protocols of chemically induced ileitis using TNBS/ethanol installation (22,23) to create a reproducible and well-tolerated porcine terminal ileitis model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4). Several studies using porcine models of intestinal inflammation showed their predictive value for drug development and diagnostic tools applied in clinical practice (Kalima et al, 1976;Kim et al, 2010;Negaard et al, 2010;Pouillart et al, 2010). Nevertheless, the application of protocols including the management of large mammals implies the use of highly specialized facilities and personnel, thus restricting the feasibility of these studies only to specialized institutes.…”
Section: Animal Models Of Inflammatory Bowel Diseasementioning
confidence: 99%
“…The TNBS concentration and contact time were selected from previous rodent studies, namely 15 mg ml −1 , 50% ethanol, 15 min (Negaard et al . ; Brenna et al . ), while the volume (100 ml) was estimated in comparison with human rectal anatomy (Gandarillas & Bas, ).To limit the passage of stools and to delimit the contact area of TNBS, a latex plug (consisting of a glove filled with sterile compress) was inserted 15 cm from the anal margin and an anal strapping (anal encirclement with temporary suture) was used to prevent anal leakage of TNBS.…”
Section: Methodsmentioning
confidence: 99%